2011
DOI: 10.3233/bd-2010-0316
|View full text |Cite
|
Sign up to set email alerts
|

Surgically placed wound catheters (SPWC) and local anaesthetic infusion in breast surgery: Efficacy and safety analysis

Abstract: Surgically placed wound catheters and local anaesthetic infusion is clinically safe in a wide range of surgical procedures on the breast and there appears to be a trend towards improved post operative pain relief. The studies analyzed in this review have several important drawbacks such as inadequate power to detect significant differences (none of them included more than 50 patients). A well designed RCT of patients undergoing breast surgery with an adequate number is of patients required to emphatically demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Remaining unexplained is why-if both treatment groups received levobupivacaine 0.25% (30 mL) infiltrated at the end of surgery-did the group with the placebo infusion demonstrate such a dramatic difference in pain and analgesic requirements within the recovery room? This irregularity calls into question the remainder of the study results, especially since a meta-analysis of four similar RCTs failed to detect a statistically significant difference between a local anesthetic and placebo infusion in any variable at any time point following breast surgery [60].…”
Section: Wound Infusionmentioning
confidence: 99%
“…Remaining unexplained is why-if both treatment groups received levobupivacaine 0.25% (30 mL) infiltrated at the end of surgery-did the group with the placebo infusion demonstrate such a dramatic difference in pain and analgesic requirements within the recovery room? This irregularity calls into question the remainder of the study results, especially since a meta-analysis of four similar RCTs failed to detect a statistically significant difference between a local anesthetic and placebo infusion in any variable at any time point following breast surgery [60].…”
Section: Wound Infusionmentioning
confidence: 99%
“…[82][83][84] In the same way, continuous LA infusion through surgically placed wound catheters can conveniently prolong the pain control with reduced side effects including sedation, nausea and vomiting. 85,86 Furthermore, the placement of continuous infusion catheters did not require additional surgical skills and the infusion pump or infusion catheter did not hinder patients during the postoperative stay. 85 Compared to other local anesthesia techniques, Bouman et al did not find any difference in pain scores between continuous paravertebral block and continuous LA infusion after oncological breast surgery, pointing out that the latter may be preferable due to the lower incidence of associated complications.…”
Section: Breast Surgerymentioning
confidence: 99%
“…85,86 Furthermore, the placement of continuous infusion catheters did not require additional surgical skills and the infusion pump or infusion catheter did not hinder patients during the postoperative stay. 85 Compared to other local anesthesia techniques, Bouman et al did not find any difference in pain scores between continuous paravertebral block and continuous LA infusion after oncological breast surgery, pointing out that the latter may be preferable due to the lower incidence of associated complications. 87 Even delivering LAs through the surgical drain may have some advantages.…”
Section: Breast Surgerymentioning
confidence: 99%
“…[4][5][6][7] A meta-analysis of surgically placed wound catheters (SPWCs) for the management of postoperative pain after breast surgery looked at 4 randomised controlled trials (RCTs) including a total of 147 women. 8 This study showed a trend towards improved pain control. Although it was poorly powered, it was encouraging in terms of the safety and efficacy of SPWCs.…”
Section: Discussionmentioning
confidence: 99%